Government Subsidies as a Risk-Sharing Policy Tool in Innovation Investment - Hao Lu; Claudia De Fuentes; Joniada Milla; Soheil Ahmadi (Institute of Labor Economics (IZA), 2022)
Current literature on the impact assessment of government innovation subsidies is mainly empirical driven and lacks an overarching theoretical model to explain the conditions under which government subsidies create positive additionalities on private R&D investment. In this paper, we present a theoretical model that treats government subsidies as a risk-sharing vehicle for private R&D activities. More importantly, we argue that positive additionalities will be more likely to occur when the subsidies are allocated based on the risk-reward condition of the project. In addition, we show that the risk-sharing effect of government subsidies is influenced by a firm's absorptive capacity and the asset specificity of the project. By showing the conditions under which subsidies create positive additionality, we provide guidance to policymakers on how to improve the effectiveness of government support for innovation.
Keywords: D50; H81; O31; O38; 330; government subsidy; additionality; R&D and innovation; the risk-sharing model; absorptive capacity; asset specificity